Epigenetic Mechanisms of Foetal Imprinting: Integrating Garbha-Sanskar with Prenatal Stress and Cognitive Development - Khavate, Manoj Mahavir; Chikane, Dipess Ramdas; Vakte, Sanket Rajendra (Asian Journal of Biological and Life Sciences, 2026)
This review focused on the transfer of memory and foetal imprinting specifically the effect of Garbha Sanskar in neurocognitive development. It talks of the interaction of the maternal stress, Hormonal milieu, nutrition and the overall psychosocial environment with epigenetic mechanisms that affect gene expression and development of neuronal networks in the developing foetus. Keywords were used to identify literature contained in key biomedical databases based on stress hormones, cortisol, memory, learning, pregnancy, maternal environment, transgenerational memory transfer, chromatin regulation, inheritance of behaviours, cognitive well-being, Garbha Sanskar, Traditional prenatal practices and meditation. Experimental literature on DNA methylation, histone modification and small RNAs in animal and cellular models is coupled with epidemiological research of prenatal stress and neurodevelopment in humans, and emerging literature about yoga, meditation and mindful interventions. The review identifies the possibility of traditional Garbha Sanskar approaches to regulate the intrauterine environment by reducing stress and achieving autonomic balance with plausible downstream epigenetic consequences that can impact cognition, emotional regulation and behaviour trajectories in offspring. The article postulates a biologically plausible correlation between prenatal behavioural interventions and neurodevelopmental later outcomes by merging Ayurvedic theories with a modern scientific view of epigenetics and neuroscience. It also finds conceptual and methodological gaps, such as a shortage of controlled human evidence regarding Garbha Sanskar as such, and requirements of longitudinal and mechanistically informed studies, incorporating clinical, behavioural and molecular endpoints. This cross-scientific viewpoint implies that a prenatal intervention that is consciously developed can be used to complement the present-day antenatal care in facilitating ideal brain development and intergenerational mental health.
Keywords: Cognitive development; Epigenetics; Foetal imprinting; Garbha-Sanskar; Memory; transfer